ВЗАИМОСВЯЗЬ ИРРАЦИОНАЛЬНЫХ УБЕЖДЕНИЙ И ЗАЩИТНЫХ МЕХАНИЗМОВ У ЖЕНЩИН, СТРАДАЮЩИХ МИГРЕНЬЮ - Светлана ТОЛСТАЯ (Moldova State University, 2020)
Мигрень - одна из самых распространенных форм головной боли. Большая распространенность мигрени среди лиц молодого трудоспособного возраста, снижение качества жизни населения ввиду социально-экономических последствий, а также трудности диагностики и терапии определяют огромный интерес к этой проблеме. В статье представлены результаты исследования особенностей защитных механизмов и иррациональных убеждений у женщин, страдающих мигренью.   THE RELATIONSHIP OF IRRATIONAL BELIEFS AND PROTECTIVE MECHANISMS IN WOMEN SUFFERING MIGRAINS Migraine is one of the most common forms of headache. The high prevalence of migraine in people of young working age, the socioeconomic consequences associated with a decrease in the quality of life of patients, and the difficulties of diagnosis and therapy determine the enormous interest in this problem. The article presents the results of a study of the characteristics of protective mechanisms and irrational beliefs in women suffering from migraine.